The Role of Strength-based Parenting in Family Sex Communication - Sumargi, Agnes Maria; Rani, Elizabeth (Universitas Muhammadiyah Metro, 2025)
Strength-based parenting is a parenting style where parents focus on children's strengths and positive qualities. This approach is generally linked to better well-being and psychological states in adolescents. However, the impact of this parenting style on how families communicate about sex remains unclear. This is a crucial issue, considering that adolescents need sex education, and parents should play a key role in providing it. This study aimed to investigate the role of strength-based parenting dimensions (strength knowledge and strength use) on family sex communication. Participants were 253 senior high school students in Surabaya who completed the Strength-Based Parenting Scale and the Family Sex Communication Quotient questionnaires. Using multiple regression analysis, the result showed that strength-based parenting influenced family sex communication. Parental encouragement for adolescents to utilize their strengths (strength use) was a significant predictor of family sex communication. This indicates that parents’ positive encouragement motivates both children and parents to engage in discussions concerning sensitive topics such as sex. Future studies should consider the social and cultural values held by the family, parental understanding of sexual issues, and adolecents’ gender.